AN IMPROVED METHODOLOGY FOR DEVELOPING STUDENTS' SPEECH BASED ON A LINGUISTICALLY FOCUSED APPROACH - Ilhomova Nafosat Ilhomovna (American Journals, 2025)
This article discusses the linguistically focused approach and an improved methodology for developing students' speech based on a linguistically focused approach.
Keywords: Speech, linguistic, linguistically focused approach, communicative approach, development of civilized speech.